Effects of Grain Refinement on The Cooling Rate, and Microstructural and Mechanical Properties of Al-Si Sand Castings - Lim, Ying Pio (2006)
This thesis covers the key areas of numerical simulation of sand casting process to evaluate the runner and gating system of sand mold. The major experimental work is focused on grain refinement and modification of LM6 A1-Si sand casting. The simulation software package used is MAGMAsoft and the sand casting process employed is COz sand casting. The numerical results of MAGMAsoft match qualitatively with the experimental data. This validates the use of MAGMAsoft to simulate sand casting process to assist in mold design and prediction of flow and solidification characteristics. The implementation of experimental work to ascertain flow and solidification characteristics of sand casting has been performed on a casting designed with varying thickness of different moduli. The casting metal used is LM6 A1-Si alloy. The cooling rate of sand casting has been correlated with the modulus of casting. The mechanical mechanical properties of hardness and ultimate tensile strength have been correlated with the solidification rate. The secondary dendrites arm spacing (SDAS) is also found to have linear correlation with section modulus. This provides important and useful information to product design of sand casting about how to optimize the section thickness to achieve the desired mechanical properties. An investigation is carried out to study how to further enhance the mechanical properties of LM6 A1-Si alloy sand casting by adding the commercial grain refiner of Al-5Ti-1B into the melt at different inoculation levels of 0.25, 0.5, 0.75 and 1.0% weight. The results show that 0.5% weight of A1-5Ti-1B grain refiner is the optimal level to grain refine and enhance the mechanical properties of LM6 sand casting. The microstructural analysis shows that grain size is reduced when the casting solidifies with faster cooling rate due to the addition of grain refiner. This renders significant effect to enhance the mechanical properties of the casting. The improvement of grain refinement is quantified by measuring the hardness, ultimate tensile strength (UTS) and elongation (strain) of the cast samples. Inoculation with 0.5% weight of Al-5Ti-1B grain refiner has attained UTS of 167.86 MPa, maximum hardness of 65.6 Rockwell and fracture strain of 0.0314. A further investigation has been carried out to add 0.5% weight of A1-1OSr and 0.5% weight of Al-5Ti-1B into the melt to cast the same part. Similar mechanical tests and microstructural analysis are performed to study the combination effect of strontium, titanium and boron on LM6 sand castings. It is discovered that the ultimate tensile strength of the castings is further improved to 174.46 MPa and the morphology has been modified. However, the hardness of Sr-modified LM6 sand casting only achieves a maximum value of 63.34 Rockwell which is not a significant improvement. Modification of LM6 by strontium only alters the morphology of the silicon eutectic to be more fibrous instead of acicular so that the structure would not be brittle relative to unmodified structure and it is found that the ductility after modification achieves a fi-acture strain of 0.032 which is higher than the 0.0267 of unmodified LM6. The cooling curve shows that the solidification is dramatically transformed to eutectic solidification at temperature around 540 O C . This mixture of grain refiner and modifier is termed "hybrid modifier" by the author.